Pengaruh Penggunaan Alat Peraga IPAS Materi Sifat-Sifat Cahaya Terhadap Hasil Belajar Siswa Kelas V di MI Terpadu Logaritma - Ni’ma Kamalia; Oky Ristya Trisnawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
Based on the research conducted at MI Terpadu Logaritma Kedungjati, Sempor District, Kebumen Regency, it can be concluded that the use of IPAS teaching aids on the topic of light properties has a significant effect on improving fifth-grade students’ cognitive learning outcomes and critical thinking skills. The statistical test results showed a significant difference between the experimental class, which used teaching aids, and the control class, which used conventional methods, with a significance value of 0.000 < 0.05. The use of teaching aids in IPAS learning helps students understand abstract concepts more concretely through observation and direct experimentation. Students became more active, enthusiastic, and able to relate scientific concepts to real-life phenomena. Thus, teaching aids function not only as instructional media but also as tools to foster learning motivation and develop students’ critical thinking skills. This study confirms that teaching aid–based learning can serve as an effective alternative to improve the quality of learning processes and outcomes in elementary schools. Teachers are expected to design and utilize simple, contextual teaching aids related to the learning material to make the learning process more meaningful and student-centered. Furthermore, the results of this study can serve as a reference for schools and educators in developing innovative, interactive, and engaging IPAS learning strategies to achieve optimal educational goals